2021
DOI: 10.3390/ijms222313032
|View full text |Cite
|
Sign up to set email alerts
|

Role and Perspectives of Inflammation and C-Reactive Protein (CRP) in Psychosis: An Economic and Widespread Tool for Assessing the Disease

Abstract: Schizophrenia is a major psychotic disorder affecting nearly 23.6 million people globally and greatly impacting the cognitive and social functioning of individuals. Multiple risk factors, including genetic, environmental, and epigenetic factors have been identified. However, the exact mechanism by which some factors aid in the development of schizophrenia is still uncertain. Acute and/or long-standing inflammation has been implicated as both a cause and effect of schizophrenia. Heightened immune responses have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Hence, the study of the composition of AH may lead to finding some biomarkers of neuroinflammation of those recently reported for some neurological diseases [ 24 ]. Consistent with the hypothesis of a neuroinflammatory component in diabetes, there was an increase in the level of kynurenine, which is related to microglial activation/neuroinflammation [ 25 , 26 , 27 ]. Our findings are consistent with the increase in 3-OH-kynurenine in the CSF of an experimental diabetic encephalopathy model in rats [ 28 ].…”
Section: Discussionsupporting
confidence: 72%
“…Hence, the study of the composition of AH may lead to finding some biomarkers of neuroinflammation of those recently reported for some neurological diseases [ 24 ]. Consistent with the hypothesis of a neuroinflammatory component in diabetes, there was an increase in the level of kynurenine, which is related to microglial activation/neuroinflammation [ 25 , 26 , 27 ]. Our findings are consistent with the increase in 3-OH-kynurenine in the CSF of an experimental diabetic encephalopathy model in rats [ 28 ].…”
Section: Discussionsupporting
confidence: 72%
“…However, despite a nonsignificant trend, we stressed that one of the best P ‐values (q‐value) was obtained in the instrumental variables from CRP of the EUR population (q‐value IVW = 0.0514, Egger intercept = 0.389). This is not surprising because several studies have suggested that CRP is a potential biomarker for diagnosis, treatment response, and prevention of SCZ 38 . Specifically, previous clinical studies, including those with a cross‐sectional design, have shown that patients with SCZ had higher CRP values compared with the control group 39–45 .…”
Section: Discussionmentioning
confidence: 95%
“…This is not surprising because several studies have suggested that CRP is a potential biomarker for diagnosis, treatment response, and prevention of SCZ. 38 Specifically, previous clinical studies, including those with a cross-sectional design, have shown that patients with SCZ had higher CRP values compared with the control group. [39][40][41][42][43][44][45] However, such a study design contains bias, which could be associated with the "status" of SCZ.…”
Section: Causal Effect Of Instrumental Variables From Nonpsychiatric ...mentioning
confidence: 99%
“…The KP pathway is initiated either by tryptophan-2,3-dioxygenase (TDO) in the liver to open the TRP indole ring, or indole-2,3-dioxygenase (IDO) in the brain to produce an instable metabolite of N -formylkynurenine [ 40 , 41 ] ( Figure 2 ). The conversion of N-formylkynyrenine to L-kynurenine (KYN) is then followed.…”
Section: The Kynurenine Pathwaymentioning
confidence: 99%